Physico-Chemical Properties and Push-Out Bond Strength to Root Dentine of Calcium Silicate-Based Sealers - Ivana Milanovic; Vesna Miletic; Bojan Dzeletovic; Djordje Antonijevic; Tatjana Savic Stankovic; Danilo Pavlovic; Ana Despotovic; Violeta Petrovic (Journal of Functional Biomaterials)
The calcium silicate-based sealers currently available on the market have different compositions and formulations, which is why their physical and chemical properties may vary. (1) The aim of the study was to measure the physico-chemical properties of calcium silicate-based sealers and their push-out bond strength to root dentine, comparing two push-out testing protocols. (2) Standardized specimens of EndoSequence BC, BioRoot RCS, MTA Fillapex, and AH Plus (control) were subjected to pH measurements over 28 days. Radiopacity was measured using a CCD sensor, and flexural strength was assessed using a three-point bending setup. Push-out bond strength was measured in coronal, middle, and apical sections of 40 single-root teeth (conventional method), and cylindrical cavities were prepared for all sealers on the same root dentine disks in 11 third molars (disk method). (3) EndoSequence BC exhibited a higher pH than MTA Fillapex and the highest radiopacity (p < 0.05). The highest flexural and push-out bond strengths were found for AH Plus. The push-out bond strength of EndoSequence BC and BioRoot RCS was higher than MTA Fillapex (p < 0.05). The conventional and disk methods exhibited similar push-out bond strength results, but the data were more homogeneously distributed in the disk method. (4) All calcium silicate-based sealers exhibited a higher pH than AH Plus. MTA Fillapex did not meet the ISO standard. Calcium silicate-based sealers showed weaker performance in terms of physical properties compared to AH Plus.